Scleractinia (Cnidaria: Anthozoa) from ECOMARG 2003, 2008 and 2009 expeditions to bathyal waters off north and northwest Spain (northeast Atlantic) - ALTUNA, ÁLVARO (Zootaxa, 2013)
Nineteen species of deep-water scleractinian corals were collected at depths between 488–1222 m during ECOMARG 2003, 2008 and 2009 expeditions to the Avilés Canyon system, Le Danois Bank (‘el Cachucho’), and Galicia Bank (north-east Atlantic). Eighteen of them were identified to species. All are previously known from the northeast Atlantic, although several are seldom reported (e.g., Aulocyathus atlanticus, Balanophyllia thalassae, Dendrophyllia alternata, Stephanocy-athus crassus). Records of Deltocyathus eccentricus and Flabellum chunii constitute northern range extensions. Six spe-cies (Caryophyllia sarsiae, Stephanocyathus crassus, Flabellum chunii, Flabellum macandrewi, Dendrophyllia alternata, Balanophyllia cellulosa) were recorded outside their previously known bathymetric ranges in the Bay of Biscay and near-by areas. Dendrophyllia alternata, Deltocyathus eccentricus and Stephanocyathus crassus are new to the “West coast of Spain and Portugal” region, here considered of high biodiversity. The bank-building species Lophelia pertusa and Madrepora oculata were abundant on Galicia Bank, and the latter was as well in the Avilés Canyon system. Both were exceedingly rare on Le Danois Bank. Among all species identified, Madrepora oculata was the most common (11 stations). The number of species collected was higher on Le Danois Bank (13 species) than on Galicia Bank (12 species) and in the Avilés Canyon system (3 species), although results may be related to sampling effort. From a literature review and new records presented herein, numbers of species known from each of the three areas total 23, 12, and 18 respectively.